University Communication About Mental Health Amid the Twin Pandemics: Text Mining and Sentiment Analysis - Anita Ciunova-Shuleska; Nikolina Palamidovska-Sterjadovska; Kimberly Parker; Sarah Geegan; Anne Amegbeha Amissah (Romanian Journal of Communications and Public Relations)
Analyzing past universities’ mental health communications to identify dominant themes and tone is crucial for improving future strategies. However, existing research has largely neglected this study area. Rooted in the framing theory and ethics of care, this paper aims to provide insights into the structure and tone of US universities’ written communication regarding student mental health amid the twin pandemics. The analysis focused on 1405 messages sent by university presidents to students from January 2016 to December 2022, divided into periods before and during the twin pandemics. Text mining and sentiment analysis assessed the content and tone of these messages. Topic analysis revealed eight topics in communication before and ten topics during the twin pandemics, with “counseling support,“ “violence,“ and “life loss” appearing in both periods. US universities communicated with a neutral tone in both periods. The research recommends prioritizing counseling support and addressing issues like violence, and loss for enhanced student services. It provides a foundation for understanding universities’ responses to mental health challenges, emphasizing the importance of ongoing assessment and adjustment of communication strategies for enhancing student mental health support. As universities are crucial for student well-being, discussions should reflect evolving changes and emerging issues.